Healthcare-associated infections according to invasive procedures in a neonatal intensive care unit - Pagano Rivera, Yda Flor (2023)
Objective. To identify the relationship between healthcare-associated infections according to invasive procedures and characterization variables in the neonatal intensive care unit of a regional referral hospital. Methods. The study had a quantitative approach, type and design of correlational study. The population consisted of 273 neonatal medical records, the sample being 160 neonatal medical records from the intensive care unit. A descriptive analysis of frequencies and percentages was performed. Results. Among the microorganisms found,15% (24) belonged to Klebsiella sp.; 11.3% (18) to Pseudomona sp.; 39.4% (63) had a hospital stay of 16 to 28 days; 53.1% (85) had low birth weight; and 80% (128) were preterm. To verify the relationship between X and Y variables, a reliability test p < 0.05 was obtained, which confrmed the relationship between health careassociated infections according to invasive procedures in the neonatal intensive care unit and the characterization variables (sex and hospital stay). Conclusions. It is concluded that health care-associated infections according to invasiveprocedures in the neonatal intensive care unit are related to respiratory access, vascular access, hospital stay, birth weight and gestational age of the neonate.